Redescription of Cyclestheria hislopi (Baird, 1859) (Crustacea: Branchiopoda: Diplostraca: Cyclestherida) from Chennai, Tamil Nadu - Sonia, R.; Ramanibai, R.; Kanniga, S. (Our Nature, 2013)
Conchostracans are commonly known as “Clam Shrimps” because their superficial resemblance with that of bivalved molluscs. There are five families established under this group and their ineterrelationships to each other are unclear until today. All of them possess a bivalved carapace with two valves joined by a strong adductor muscle. Reduced abdomen and their ability to be completely enclosed within a bivalved carapace is the key and unique character which isolate this group from other anostracans and notostracans. DOI: http://dx.doi.org/10.3126/on.v10i1.7797